Analiza i klasyfikacja danych w aspekcie współczynnika Z - Meus, Jan; Stefaniak, Justyna (Analysis and Data Classification in the Aspect of Coefficient Z, 2005)
Publications dedicated to the analysis of contingency tables in statistical literature focus frequently on establishing statistical significance between investigated variables. It leads to treating them as single states, though these variables are usually defined as systems of events creating the specific one. The reason of this approach is in the lack of method which would treat both variables as a system of two systems of disjoint events and would introduce the analysis of the "interior" structure of the data. In this paper a new asymmetrical measure of dependence has been introduced which bases on the above mentioned assumption.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 485-492